Percepção, alucinação, sonho diurno, esperança e utopia: aproximações entre Merleau-Ponty e Ernst Bloch - Figueiredo, Jadismar de Lima (2021)
The present work aims to study the theme of hallucination and Utopia. Its main objective is to analyze the concepts of hallucination and perception in Merleau-Ponty and the principle of hope and daydream in Ernst Bloch to conceive the hallucinatory and utopian experience as effective in a horizon of hope for human life. The conducting hypothesis of the research is consolidated in the question that even though in Merleau-Ponty perception and hallucination are different experiences, both are ways of connecting the subject to the world through perceptual experience In this sense, it is possible to think a certain continuity between perception and hallucination in insofar as both preserve the initial and permanent condition of man, which is to be connected to the world by his own body. In Ernst Bloch, the daytime dream opens up as a horizon of hope for the future to come true. Thus, driven by hope, dreams and desires can be the result of a utopia, which is shown as a construction of dreams approaching perception and hallucination, maintaining the strengthening of the discussion. There is also a continuity with the hope principle in Bloch, as both face a prospecting problem, whether from the past to the present, or from the present to the future. Hallucination, therefore, is related to perception, hope and daytime dream, therefore, this thesis defends that the hallucinatory experience is effective and in utopia there are hallucination traces, creating a horizon of possibilities for its realization, motivated by intentionality and hope.